The effects of supervisor support and self-efficacy on call center employees’ work engagement and quitting intentions - Ibrahim, Siti Nur Hidayah; Choo, Ling Suan; Karatepe, Osman M. (Emerald Publishing Limited, 2019)
Purpose – The purpose of this paper is to examine whether the differences in men and women, such as risk aversion in decision making, can influence the amount of capital that the board of directors can allocate for investment opportunities. Design/methodology/approach – This study sampled 212 IPOs over the period of 2005–2015 and employed the OLS and the quantile regression techniques to examine the impact of female directors on capital allocation. Findings – The results show that women on corporate boards have a positive influence on the amount of capital an IPO company can allocate for investment opportunities. These findings suggest that the investment strategies of women in an emerging financial market, like Malaysia, may differ from women in other financial markets. Practical implications – The presence of women on corporate boards plays an important role in board involvement in a company’s strategic decision at the time of the IPO. Therefore, regulators and IPO issuers should pay close attention to the corporate governance structure of a company at the time of an IPO. In addition, investors and other stakeholders of a company may consider women on corporate boards as an important factor in financing and investment decisions. Originality/value – Despite several studies that have examined the influence of women on corporate boards on corporate outcomes, globally, the presence of women on corporate boards and their influence on corporate decision-making related to allocation of capital to investment opportunities, have not been fully explored in the IPO literature.